Power Point-Based Educational Game on Science Learning to Support Elementary School Students' Learning Activities - Levitasari, Anggita Nur; Cahyadi, Fajar; Rofian, Rofian (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
Technological developments also have an impact on the world of education. Teachers to be able to use technology to create learning that is fun, interactive,and motivating. The purpose of this study is to determine the response of teachers and students as well as the effectiveness of interactive learning media PowerPoint game . This study uses Research and Development research using the ADDIE model, namely through the stages of analysis, design, development, implementation, and evaluation as research steps. Data collection is done by observation, interviews, expert validation, and questionnaires. The developed interactive learning media receives high feasibility ratings, with material experts, media experts, and linguists affirming its validity and suitability for testing. Student responses indicate strong engagement and interest, while teacher feedback underscores its potential as a valuable learning tool. Quantitative analysis of student learning outcomes reveals a significant improvement, with an average increase of 60.60%. Thus, the developed interactive learning media proves effective in enhancing student learning outcomes. The study advocates for the incorporation of this media into the school curriculum, emphasizing the importance of teacher guidance to optimize its utilization. Furthermore, it encourages ongoing development to align with technological advancements, ensuring continuous improvement in interactive learning experiences.